AN ANALYSIS OF THE IMPLEMENTATION OF QUESTIONING STRATEGY IN EFL LEARNING DURING COVID-19 PANDEMIC - Dodik Wiratama, Dewa Ngakan Putu; Padmadewi, Ni Nyoman (Language and Education Journal Undiksha, 2022)
This study aimed to analyze the types of questions used by the teacher and how the questioning strategy is implemented in EFL learning and analyze students’ opinions toward the implementation of questioning strategy in EFL learning conducted at SMAN 1 Sukawati during the pandemic situation. The English teacher and the twelfth-grade students at SMAN 1 Sukawati was the subject of this study. This study used an embedded mixed-method design with qualitative dominant. This study showed that the teacher used all types of questions proposed by Richard & Lockhart (1996) and Padmadewi et al. (2017). Those are procedural, divergent, convergent, compliance, rhetorical, prompting, and probing questions. The result also showed that the teacher frequently used low-order questions in EFL learning. Those questions occurred in three sessions; pre-activity, main activity, and post-activity. Further, there were two learning management system used by the teacher, namely WhatsApp and Google Form. Besides, the implementation of the questioning strategy also got positive responses from most of the students because it creates a better quality of teaching and learning process.